2021
DOI: 10.1101/2021.03.20.436273
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistent cell migration emerges from a coupling between protrusion dynamics and polarized trafficking

Abstract: Migrating cells present a variety of paths, from non-persistent random walks to highly directional trajectories. While random movement can be easily explained by an intrinsic basal activity of the cell, persistent movement requires the cell to be stably polarized. It remains unclear how this is achieved from the regulation of underlying subcellular processes. In the context of mesenchymal migration, the ability of cells to migrate persistently over several hours require a mechanism stabilizing their protruding… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Up to now, the optogenetic approaches that have been developed to control GTPases in space and time tended to confirm the canonical picture. For example, we and others have shown that for Rac1 and Cdc42, despite of a complex cross-activation, the recruitment at the plasma membrane of minimal GEF activating domains causally induce cell protrusions 9 and migration led by the front 10 . Along the same line, optogenetic approaches to control RhoA, reviewed in 11 and 12 , have all shown a causal induction of cell retraction.…”
Section: Introductionmentioning
confidence: 91%
“…Up to now, the optogenetic approaches that have been developed to control GTPases in space and time tended to confirm the canonical picture. For example, we and others have shown that for Rac1 and Cdc42, despite of a complex cross-activation, the recruitment at the plasma membrane of minimal GEF activating domains causally induce cell protrusions 9 and migration led by the front 10 . Along the same line, optogenetic approaches to control RhoA, reviewed in 11 and 12 , have all shown a causal induction of cell retraction.…”
Section: Introductionmentioning
confidence: 91%
“…Luo et al [114] produced UV functionalized TiO 2 nanorods micropattern in various configurations, including concentric, linear, honeycomb-like, square, and gem-like stripes (each with a width of 30 µm) and demonstrated Nucleus-Golgi axis [96] as factors associated with cell polarization.…”
Section: Cell Polarizationmentioning
confidence: 99%
“…These experiments require overexpression of the signaling molecules fused to SspB but also the target protein, which by itself might already have a signaling effect. iLID is widely used and often in combination with a plasma membrane tag (Dessauges et al, 2022; Gonzalez-Martinez et al, 2022; Saha et al, 2022; Vaidžiulytė et al, 2022). The approach can be improved by targeting proteins to a more specific location, for example recruiting to focal adhesions or adherens junctions where local GEF and GAP activity have been detected (Müller et al, 2020).…”
Section: Introductionmentioning
confidence: 99%